A long survival of a patient with brain metastasis of unknown site of the primary tumor - Ben Kridis, W.; Sghaier, S.; Toumi, N.; Boudawara, Z.; Khanfir, A.; Daoud, J.; Frikha, M. (Experimental Oncology, 2018)
Eighty percent of brain metastases (BM) are diagnosed in patients with known primary site of cancer. BM of unknown primary represents a difficult diagnosis. In up to 15% of patients with BM, the site of the primary tumor will not be detected despite investigations. The prognosis of this entity is very poor. We report here a case of a long survival of a patient with brain metastasis of unknown primary. The conclusion that can be drawn is that within BM of unknown primary exist patients with a very good prognosis that must be collected and published in order to base recommendations.